Ileal Atresia in a Preterm Neonate Complicated by Necrotizing Enterocolitis: A Case Report - Ariadne Tiara Hapsari; Andika Eka Nugroho; Desi Yulyanti (Medical and Health Journal, 2026)
Background: Ileal atresia is a congenital intestinal obstruction that frequently affects premature neonates and is associated with high morbidity, particularly when complicated by necrotizing enterocolitis (NEC) and sepsis. Optimal outcomes depend not only on surgical intervention but also on comprehensive perioperative management by a multidisciplinary team, particularly neonatologists. Case Presentation: We report a male preterm neonate born at 32 weeks and 5 days of gestation with progressive abdominal distension, bilious gastric residue, and failure to pass meconium. Initial respiratory distress improved with non-invasive ventilation. However, gastrointestinal deterioration occurred on day four of life, with radiographic findings consistent with NEC stage III and pneumoperitoneum. Emergency laparotomy revealed ileal atresia, and staged surgical management was performed. Discussion: The pediatric or neonatal team played a crucial role in preoperative stabilization, including respiratory support, fluid and electrolyte correction, broad-spectrum antibiotics, and nutritional optimization. Postoperatively, close monitoring of respiratory status, infection control, gradual advancement of enteral nutrition, and growth assessment enabled recovery without major complications. Full oral feeding was achieved, and the patient was discharged in stable condition on day 27 of life. Conclusion: This case highlights the pivotal role of pediatricians or neonatologists in perioperative management of ileal atresia in premature neonates, emphasizing that meticulous supportive care significantly contributes to favorable surgical outcomes.